2013
DOI: 10.3109/s10165-012-0630-0
|View full text |Cite
|
Sign up to set email alerts
|

Serum amyloid A (SAA) induces pentraxin 3 (PTX3) production in rheumatoid synoviocytes

Abstract: Our data suggest that SAA plays a role in the proinflammatory and immune responses in rheumatoid synovium by inducing PTX3. We provide the first evidence that the acute-phase reactant SAA, which is produced systemically by hepatocytes, perpetuates the rheumatoid inflammatory processes by inducing another proinflammatory molecule, PTX3, locally in rheumatoid synovial tissues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…As previously reported by our group, steroid treatment might have opposite effects on the release of PTX3 by different cell types involved in the same inflammatory microenvironment, PTX3 expression being for example inhibited in myeloid cells and upregulated in fibroblasts and endothelial cells (32), illustrating the complexity of PTX3 production balance in response to therapies. Also, as reported by Satomura and colleagues, PTX3 expression is enhanced by other acute-phase reactants, such as SAA produced by hepatocytes, independently of treatment influence (33). Accordingly, we observed a positive correlation between SAA and PTX3 synovial transcripts abundance in our cohort.…”
Section: Discussionsupporting
confidence: 89%
“…As previously reported by our group, steroid treatment might have opposite effects on the release of PTX3 by different cell types involved in the same inflammatory microenvironment, PTX3 expression being for example inhibited in myeloid cells and upregulated in fibroblasts and endothelial cells (32), illustrating the complexity of PTX3 production balance in response to therapies. Also, as reported by Satomura and colleagues, PTX3 expression is enhanced by other acute-phase reactants, such as SAA produced by hepatocytes, independently of treatment influence (33). Accordingly, we observed a positive correlation between SAA and PTX3 synovial transcripts abundance in our cohort.…”
Section: Discussionsupporting
confidence: 89%
“…PTX3 is also an acute-phase reactant involved in amplification of the inflammatory response. This loop seems to involve N-formyl peptide receptor ligand-1 (FRLP-1) (158).…”
Section: Saa In Rheumatic Diseasesmentioning
confidence: 99%
“…In rheumatoid synoviocytes transcription of the PTX3 messenger RNA (mRNA) was found to be directly promoted by serum amyloid A [75]. Moreover, plasma analysis and gene expression profile revealed that PTX3 might be involved in the remote cardioprotective effects observed in mice after subcutaneous transplantation of heme oxygenase-1-overexpressing mouse mesenchymal stem cells [76].…”
Section: Ptx3 In Cardiovascular Diseasesmentioning
confidence: 99%